Therapeutic Hypothermia and Out-of-Hospital Cardiac Arrest in a Child with Hypertrophic Obstructive Cardiomyopathy - Nancy Spurkeland; Gregory Bennett; Chandran Alexander; Dennis Chang; Gary Ceneviva (Case Reports in Pediatrics)
Neurologic outcomes following pediatric cardiac arrest are consistently poor. Early initiation of cardiopulmonary resuscitation has been shown to have positive effects on both survival to hospital discharge, and improved neurological outcomes after cardiac arrest. Additionally, the use of therapeutic hypothermia may improve survival in pediatric cardiac arrest patients admitted to the intensive care unit. We report a child with congenital hypertrophic obstructive cardiomyopathy and an out-of-hospital cardiac arrest, in whom the early initiation of effective prolonged cardiopulmonary resuscitation and subsequent administration of therapeutic hypothermia contributed to a positive outcome with no gross neurologic sequelae. Continuing efforts should be made to promote and employ high-quality cardiopulmonary resuscitation, which likely contributed to the positive outcome of this case. Further research will be necessary to develop and solidify national guidelines for the implementation of therapeutic hypothermia in selected subpopulations of children with OHCA.